Relational Marketing Strategy Based On Social Capital And Sharia Values At BMT UGT Sempu - M. Finanda Prayoga; Lely Ana Ferawati Ekaningsih (proceedings.icesy, 2026)
Baitul Maal wat Tamwil (BMT) is essential for inclusive finance, yet it encounters difficulties in establishing a viable marketing approach. This qualitative case study seeks to examine the marketing strategy and its enabling factors at BMT UGT Sempu. The findings indicate that BMT UGT Sempu employs a relational marketing strategy that transforms local benefits such as geographic and cultural closeness, Islamic principles, and robust social capital into central value offerings. Islamic values form the basis of trust, whereas social capital functions as the underlying framework that enables transactions. The research concludes that BMT’s long-term viability is bolstered by its capacity to merge sharia principles and social capital into a marketing approach that resonates with the socio-cultural traits of the community. These outcomes contribute to the existing body of knowledge on sharia financial services marketing by presenting a contextual framework from the viewpoint of microfinance institutions.